Editorial: A granular approach to internalizing disorders in adolescents: Examining developmental pathways and environmental influences to identify high‐risk youth - Pablo Vidal‐Ribas (JCPP Advances)
Abstract Adolescence is a critical developmental period during which internalizing disorders, such as depression and anxiety, frequently emerge. This editorial highlights six studies from this issue that investigate the complex interplay of genetic, physiological, cognitive, social, and environmental factors contributing to these disorders. By employing robust methods, these studies inform on mechanisms and trajectories, enhancing the identification of high‐risk individuals for targeted interventions. Together, these studies emphasize the importance of nuanced, multi‐factorial approaches in advancing research and practice in adolescent internalizing psychopathology. Nevertheless, future research must prioritize diverse samples, dynamic longitudinal designs, and multi‐informant approaches to increase generalizability and impact.